Pengaruh perspektif waktu (time perspective) terhadap kualitas relasi sosial - Evanytha, Evanytha (Konsorsium Psikologi Ilmiah Nusantara, 2012)
One important and basic aspect of human subjective experience is time.Existentialists stated that humans are beings who exist in relation to a specific time andplace, and specific meaning. Time is an element of human existence, which underlies and regulate individual social behavior. The objective of this study was to examine the effect of time perspective on quality of social relation. Participants were 96 undergraduate students. This study used Zimbardo Time Perspective Inventory and Positive Relation with Others scales. The ZTPI contains five dimensions: Past-Positive, Past-Negative, Present-Hedonistic, Present-Fatalistic and Future. Data analysis used multiple regression. The result showed there was effect of five dimensions of time perspective on quality of social relation. Dimensions of Past-Positive and Future partially had significant effect on quality of social relation.